2019
DOI: 10.3390/nu11010143
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Its Human Metabolites—Effects on Metabolic Health and Obesity

Abstract: Resveratrol is one of the most widely studied polyphenols and it has been assigned a plethora of metabolic effects with potential health benefits. Given its low bioavailability and extensive metabolism, clinical studies using resveratrol have not always replicated in vitro observations. In this review, we discuss human metabolism and biotransformation of resveratrol, and reported molecular mechanisms of action, within the context of metabolic health and obesity. Resveratrol has been described as mimicking calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
184
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(213 citation statements)
references
References 108 publications
2
184
0
1
Order By: Relevance
“…37 Once Res enters the gastrointestinal tract, most was proccessed through enterocytes of small intestine, 38 in which the molecule was conjugated with sulfate or glucuronate by sulfotransferases or uridine 5′-diphospho-glucuronosyltransferases (UGTs), repectively, 39,40 with distribution into different organs, leading to consequences for its bioavailability and activity. 30 Though some studies on Res metabolites showed effect on autophagy, 41,42 as shown in our data and other studies, 43,44 these metabolites had less effect compared with its origin form on metabolism. In the current study, Res metabolites were applied in insulin resistant 3T3-L1 adipocyte to explore their potential effects.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…37 Once Res enters the gastrointestinal tract, most was proccessed through enterocytes of small intestine, 38 in which the molecule was conjugated with sulfate or glucuronate by sulfotransferases or uridine 5′-diphospho-glucuronosyltransferases (UGTs), repectively, 39,40 with distribution into different organs, leading to consequences for its bioavailability and activity. 30 Though some studies on Res metabolites showed effect on autophagy, 41,42 as shown in our data and other studies, 43,44 these metabolites had less effect compared with its origin form on metabolism. In the current study, Res metabolites were applied in insulin resistant 3T3-L1 adipocyte to explore their potential effects.…”
Section: Discussionsupporting
confidence: 43%
“…Furthermore, controversy may be partially attributed to nonphysiological concentrations used and resveratrol metabolites . Once Res enters the gastrointestinal tract, most was proccessed through enterocytes of small intestine, in which the molecule was conjugated with sulfate or glucuronate by sulfotransferases or uridine 5′‐diphospho‐glucuronosyltransferases (UGTs), repectively, with distribution into different organs, leading to consequences for its bioavailability and activity . Though some studies on Res metabolites showed effect on autophagy, as shown in our data and other studies, these metabolites had less effect compared with its origin form on metabolism.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Resveratrol (RSV) is a pleiotropic phytochemical found in peanuts and grapes that has been indicated to provide a wide range of health benefits, such as reducing oxidative, inflammatory, and apoptotic signals [122]-protecting against neurological decline [123], improving cardiovascular health [124], ameliorating diabetes [125], and preventing cancer [126]. The anticancer properties of RSV act through diverse molecular mechanisms that have been investigated in a plethora of cellular and animal models [127,128]…”
Section: Resveratrolmentioning
confidence: 99%